2006
DOI: 10.1111/j.1462-2920.2006.01084.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyanobacterial assimilatory nitrate reductase gene diversity in coastal and oligotrophic marine environments

Abstract: Cyanobacteria are important primary producers in many marine ecosystems and their abundances and growth rates depend on their ability to assimilate various nitrogen sources. To examine the diversity of nitrate-utilizing marine cyanobacteria, we developed PCR primers specific for cyanobacterial assimilatory nitrate reductase (narB) genes. We obtained amplification products from diverse strains of cultivated cyanobacteria and from several marine environments. Phylogenetic trees constructed with the narB gene are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…Most of the sub-clade IV-B sequences were obtained from a near-shore station at the chlorophyll maximum. Two distinct Clade IV clusters were also observed using environmental sequences of the nitrate reductase gene (narB) from Monterey Bay, California (Jenkins et al 2006). It is likely that these Clade IV clusters are from the same Synechococcus types observed with the rpoC1 sequence phylogeny.…”
Section: Coastal To Open-ocean Transectmentioning
confidence: 74%
“…Most of the sub-clade IV-B sequences were obtained from a near-shore station at the chlorophyll maximum. Two distinct Clade IV clusters were also observed using environmental sequences of the nitrate reductase gene (narB) from Monterey Bay, California (Jenkins et al 2006). It is likely that these Clade IV clusters are from the same Synechococcus types observed with the rpoC1 sequence phylogeny.…”
Section: Coastal To Open-ocean Transectmentioning
confidence: 74%
“…Such waters are enriched in oxidized N compounds, mostly nitrate, and ntcA expression data show that Synechococcus populations have adapted to assimilate these compounds (150,151). Nitrate utilization is widespread among oceanic and coastal Synechococcus strains, and phylogenies based on narB sequences have revealed new clades with a distinct geographic distribution (127).…”
Section: Nutrient Acquisition Nitrogen Nutritionmentioning
confidence: 99%
“…Direct measurements of NO − 3 assimilation into phytoplankton (Dugdale and Goering, 1967), nitrate reductase enzyme activity (Eppley et al, 1969), and more recent nucleic acid-based methods for detecting nitrate reductase-encoding genes (Jenkins et al, 2006;Paerl et al, 2008;Ward, 2008) and gene transcripts (Paerl et al, 2012) have all shown the importance and prevalence of nitrate-reducing activity in marine phytoplankton and the potential for NO − 2 production. None of these methods, however, address how much NO − 2 is released into the water column, where it is detected in the dissolved phase, versus how much remains in the cell.…”
Section: Introductionmentioning
confidence: 99%